ANALYSIS OF THE ABILITY OF THE FIRST YEAR STUDENTS OF SMK TIGAMA PEKANBARU IN COMPREHENDING RECOUNT TEXT - Aghnia Aristya Riandini; Erni Erni; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract:This research is aimed to find outthe Ability of the First Year Students of SMK Tigama Pekanbaru in Comprehending Recount Texts. The population of this research is the first year students of SMK Tigama Pekanbaru. The number of sample is 31 students selected by using cluster random sampling technique.The research instrument was multiple choice test items consisted40 questions. The test gives by useseight components of comprehending recount textnamely main idea, factual information, meaning of difficult word, reference, restatement, social function of recount text, generic structures of recount text and language features of recount text. The data were analyzed by classifying them into four levels of mastery, such as poor, average, good, and excellent. The findings revealed that the Analysis of the Ability of the First Year Students of SMK TigamaPekanbaru in Comprehending Recount Texts was in good level with the mean score was 60.4. The implication of thisresearch is even though the first year students of SMK TigamaPekanbaruRiau have a good ability but the score is still low, then it can be suggested for students to get more lessons about comprehending.Key Words: Students’ ability, Comprehending recount text